PENGARUH PENDEKATAN OPEN-ENDED TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN MOTIVASI BELAJAR - Husniah, Giny Nuraeni; Maulana, M.; Isrok'atun, I. (Jurnal Pena Ilmiah, 2017)
The low rate of problem solving ability and student learning motivation are the one of background of this research. The purpose of research is to know the influence of open ended approach against that. This is research used experimental method. The sample of this research is the five grade students in Gunungsari I elementary school as the experimental group and Ranjikulon I elementary school as the control group. The result of this research is: (1) open ended approach affect the ability of problem solving and student learning motivation; (2) mathematical learning with open ended approach is better than conventional approach in term of increase the problem solving ability and student learning motivation; (3) there is a positive relationships between problem solving ability and student learning motivation; and (4) the supporting factor of learning using open ended approach is the teacher’s ability in presenting open problem, observation, and interview. Meanwhile the inhibiting factors is that the student not used to the open problem.